Economic Empowerment Of Creative Wood Craftsman Communities Through The Establishment Of Communal Branding Based On Local Wisdom - Rianto, Oleh: Budi; Lestari, L. Tri (Journal of Ecohumanism, 2024)
The purpose of this study is to analyze the economic empowerment of the Creative Wood Craftsmen Association in Ngawi Regency, through the development of their production brand based on local wisdom. The research method used is action research, using the design thinking method (Kelly & Brown, 2018) starting from: (1) Empathize, (2) Define, (3) Ideate, (4) Prototype and (5) Test, in developing the brand name of creative wood products of the Ngawi Creative Wood Craftsmen Association. In capturing the participation of the empowered community, which is carried out in stages, starting with a Focus Group Discussion with the main stakeholders in Ngawi, creative wood craftsmen community leaders, the core administrators of the Creative Wood Craftsmen Association, to FGD with representatives of all members of the Creative Wood Craftsmen Association. The results of the study indicate that the formation of a participatory agreement from the Ngawi creative wood association on the brand image of creative wood products, the Establishment of the Ngawi Brand Name with the name "Papinkra" Ngawi, the Papinkra Tagline "Creative Wood", the New Vision "Becoming an International Class Creative Wood Craftsman", produced an output of a new brand name based on local wisdom consisting of 1. Logo, 2. Letterhead, 3. Product Catalog, 4. Stamp, and 5. Label as a brand image of creative wood products that will be used in expanding product marketing both online and offline.